SARVEPALLI RADHAKRISHNAN’S APPROACH TO EDUCATION (American Journal of Research in Humanities and Social Sciences, 2025)
The socio-philosophical foundations of Sarvepalli Radhakrishnan’s concept of social justice hold significant importance in the relationship between the state and the citizen. Sarvepalli Radhakrishnan was not only a philosopher but also a statesman. In his philosophical, socio-political, and moral-educational views, he drew upon Indian philosophical teachings as well as rational contemplation.This article scientifically analyzes the thinker’s views on education, his attitude towards Indian education and the ideas in his philosophy, his theories, moral perspectives, and socio-political opinions, with particular emphasis on relevant materials.